Effect of Gamma Irradiation on Survival of Pathogenic Bacteria Salmonella typhimurium, and Escherichia coli on Chicken Meat - Yuny Erwanto; Soemitro Djojowidagdo; Kapti Rahayu; Lidya Andini (Faculty of Animal Science, Universitas Gadjah Mada, 2000)
Artikel dalam bentuk PDF